2014
DOI: 10.1111/pme.12388
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pain and Comorbidity Among Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn Veterans

Abstract: The operational definition of chronic pain used in this study may have research implications for examining predictors of incident and chronic pain. These data have important clinical implications in that addressing comorbid conditions of persistent pain may improve adaptive coping and functioning in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 28 publications
8
110
1
Order By: Relevance
“…In particular, they had the highest adjusted odds of being in the combined back and arthritis/joint pain group. This is consistent with recent Veteran data demonstrating that those with persistent pain were more likely to report comorbid conditions, including diagnoses of mood disorders, PTSD, substance use disorders, anxiety disorders, and traumatic brain injury; they were also more likely to have a BMI consistent with overweight/obesity [33]. Other research has shown that those with multiple painful conditions have a number of additional medical and mental health comorbidities, along with higher burden of illness and cost of care [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, they had the highest adjusted odds of being in the combined back and arthritis/joint pain group. This is consistent with recent Veteran data demonstrating that those with persistent pain were more likely to report comorbid conditions, including diagnoses of mood disorders, PTSD, substance use disorders, anxiety disorders, and traumatic brain injury; they were also more likely to have a BMI consistent with overweight/obesity [33]. Other research has shown that those with multiple painful conditions have a number of additional medical and mental health comorbidities, along with higher burden of illness and cost of care [34].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, patients with comorbid mental health conditions, including depression and PTSD, were more likely than those without the conditions to report being in the groups with pain (the back pain only, arthritis/joint pain only, and both back and arthritis/joint pain groups) relative to the "no pain" group, a finding that is consistent with existing data describing Veterans with chronic pain [33,[35][36][37][38]. However, those patients reporting comorbid schizophrenia were less likely to report back pain or arthritis/joint pain.…”
Section: Discussionsupporting
confidence: 87%
“…Dependence to prescribed painkillers is also specifically studied in American war veterans who may have at the same time combat exposure PTSD and pains that require pharmacological treatment. In those studies, a diagnosis of PTSD or its severity appears as a risk factor of prolonged pain, of opioid use, and of opioid dependence [40][41][42][43]. But on the other hand, a toxic effect of chronic heroin use leading to secondary anxiety disorder is also observed.…”
Section: Opiatesmentioning
confidence: 94%
“…Stress and stress-related anxiety could also influence TBI outcome as people who exhibited high levels of acute stress symptoms and anxiety had poor TBI outcome (23). A significant portion of the US military personnel returning from Iraq and Afghanistan battlefields have experienced persistent somatic pain, as well as comorbidity of mild traumatic brain injury (mTBI) and post-traumatic stress disorder (PTSD) (2430). In a logistic regressions study of 2,348 veterans of Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF) (51% female), Iverson et al (31) reported significant associations between probable TBI, symptomatic anxiety, and symptomatic physical health in both genders.…”
Section: Introductionmentioning
confidence: 99%